Design of Linear and Cyclic Mutant Analogues of Dirucotide Peptide (MBP82–98) against Multiple Sclerosis: Conformational and Binding Studies to MHC Class II - George Deraos (Brain Sciences, 2018)
Background: Multiple sclerosis (MS) is an autoimmune disorder of the central nervous system. MS is a T cell-mediated disease characterized by the proliferation, infiltration, and attack of the myelin sheath by immune cells. Previous studies have shown that cyclization provides molecules with strict conformation that could modulate the immune system. Methods: In this study, we synthesized peptide analogues derived from the myelin basic protein (MBP)82⁻98 encephalitogenic sequence (dirucotide), the linear altered peptide ligand MBP82⁻98 (Ala91), and their cyclic counterparts. Results: The synthesized peptides were evaluated for their binding to human leukocyte antigen (HLA)-DR2 and HLA-DR4 alleles, with cyclic MBP82⁻98 being a strong binder with the HLA-DR2 allele and having lower affinity binding to the HLA-DR4 allele. In a further step, conformational analyses were performed using NMR spectroscopy in solution to describe the conformational space occupied by the functional amino acids of both linear and cyclic peptide analogues. This structural data, in combination with crystallographic data, were used to study the molecular basis of their interaction with HLA-DR2 and HLA-DR4 alleles. Conclusion: The cyclic and APL analogues of dirucotide are promising leads that should be further evaluated for their ability to alter T cell responses for therapeutic benefit against MS.